Object-oriented modeling of thoracic fluid balance to study cardiogenic pulmonary congestion in humans. (October 2019) - Ngo, Chuong; Dahlmanns, Stephan; Vollmer, Thomas; Misgeld, Berno; Leonhardt, Steffen
Highlights: The first biophysical computational model of fluid balance between pulmonary capillaries and lung interstitium. The first approach of an object-oriented model for the lymphatic system. The first comprehensive model to include the respiratory, the circulatory, and fluid exchange systems for an advanced description of cardiogenic congestion. Its ability to demonstrate the effect of mechanical ventilation on extravascular fluid clearance. Abstract: Background and objective: We hypothesized that a biophysical computational model implemented in an object-oriented modeling language (OOML) would provide physiological information and simulative data to study the development and treatment of cardiogenic pulmonary congestion. Methods: This work is based on the object-oriented cardiopulmonary interaction introduced in [1]. This paper describes the novel model components required to study cardiogenic pulmonary congestion: i) interstitial fluid exchange related to the Starling equation, ii) the lymphatic pump, and iii) the interconnection of these elements with the original cardiopulmonary model. The presented model succeeds in i) describing lymphatic flow at the capillary artery and venous end, ii) activation of the lymphatic pump at elevated pulmonary pressures, and iii) the simulation of the different safety factors related to lung tissue, osmotic gradient, and the lymphatic system during the development of lung congestion. Results: Simulations show a qualitative correlation between model behavior and physiological data from literature. The model also demonstrates the beneficial effect of continuous positive airway pressure therapy on fluid clearance and respiratory mechanics. Conclusion: This study demonstrates the successful use of OOML to describe the development of cardiogenic congestion by introducing a model of the lymphatic system and the thoracic fluid balance system, as well as connecting them to the existing cardiopulmonary model.